Optimalisasi Potensi Lokal melalui Pemberdayaan UMKM untuk Kesejahteraan Rumah Tangga - Atika Riasari (Universitas Veteran Bangun Nusantara Sukoharjo, 2024)
In 2020, there were approximately 14,000 UMKM in Metro City. The most dominant UMKM products in Metro City are food products and handicrafts. The issue and focus of empowerment based on existing conditions is to guide UMKM owners to carry out promotional activities through social media, add logos, create banners with directions and add locations to Google Maps.This study aims to identify local potential that can be optimized to support UMKM development, as well as provide training and assistance to the community regarding the management of UMKM based on local potential. In addition, this study also aims to increase the capacity of the community in creating high economic value products from local potential. This study is expected to formulate a community empowerment strategy through UMKMs that is effective in increasing household income and welfare, as well as building a collaboration model between the community, government, and stakeholders to support the development of UMKMs in a sustainable manner. This study uses a qualitative descriptive research method with a participatory approach. The results of the empowerment that we carried out were that business owners could carry out promotions independently, make packaging more attractive by adding logos and locations that were easier to find.